AUTOIMMUNE EPIDERMAL BLISTERING DISEASES - Ana Maria Abreu Velez; Juliana Calle; Michael S. Howard (Our Dermatology Online, 2013)
Autoimmune bullous skin diseases (ABDs) are uncommon, potentially fatal diseases of skin and mucous membranes which are associated with deposits of autoantibodies and complement against distinct molecules of the epidermis and dermal/epidermal basement membrane zone (BMZ). These autoantibodies lead to a loss in skin molecular integrity, which manifests clinically as formation of blisters or erosions. In pemphigus vulgaris, loss of adhesion occurs within the epidermis. The pioneering work of Ernst H. Beutner, Ph.D. and Robert E. Jordon, M.D. confirmed the autoimmune nature of these diseases. Walter F. Lever, M.D. contributed significantly to our understanding of the histopathologic features of these diseases. Walter Lever, M.D. and Ken Hashimoto, M.D. contributed electron microscopic studies of these diseases, especially in pemphigus vulgaris and bullous pemphigoid. In bullous pemphigoid (BP), linear IgA bullous dermatosis, epidermolysis bullosa acquisita (EBA) and dermatitis herpetiformis (DH), loss of adhesion takes place within or underneath the BMZ. Classic EBA demonstrates extensive skin fragility; DH is commonly associated with gluten-sensitive enteropathy, and manifests clinically with pruritic papulovesicles on the extensor surfaces of the extremities and the lumbosacral area. The clinical spectrum of bullous pemphigoid includes tense blisters, urticarial plaques, and prurigo-like eczematous lesions. Pemphigoid gestationis mostly occurs during the last trimester of pregnancy, and mucous membrane pemphigoid primarily involves the oral mucosa and conjunctivae and leads to scarring. Linear IgA bullous dermatosis manifests with tense blisters in a "cluster of jewels"-like pattern in childhood (chronic bullous disease of childhood) and is more clinically heterogeneous in adulthood. Many of the autoantigens in these disorders are known and have been well characterized. ABDs may be influenced by both genetic and exogenous factors. The diagnoses of ABDs is based on histology of lesional skin and direct immunofluorescence (DIF) of perilesional skin, as well as by serologic confirmation of autoantibodies by indirect immunofluorescence (IIF) and recombinant autoantigens. The titers of the autoantibodies may correlate with the disease severity, and can be measured by indirect immunofluorescence and by ELISA testing. Therapeutically, systemic treatment with glucocorticoids is combined with immunosuppressive adjuvants which allow for fast reduction of systemic steroids. A prospective clinical trial in pemphigus showed that adjuvant treatment with azathioprine, mycophenolate mofetil and cyclophosphamide led to a significant reduction of the cumulative dose of systemic steroids until complete clinical remission was achieved. In bullous pemphigoid, topical treatment with clobetasol can help to accomplish a clinical remission without the major side effects seen with systemic steroids. Also, therapeutic depletion of B lymphocytes by rituximab has considerably improved the overall prognosis of pemphigus. Nurses and other paramedical personal caring for patients with these disorders play a critical role in improving the quality of life of the patients and their families. The patients need to be continuously evaluated to avoid secondary infections, especially if they have long term immuosupressive treatment.